Effects of processing procedures and cultivar on the properties of cassava flour and starch - Fernandez, Alejandro Q. (1996)
The aim of this research was to widen the knowledge of the physicochemical properties of cassava starch and flour and to understand the factors which influence their functional characteristics, including both genetic and environmental effects as well as processing procedures. A range of chemical and physical techniques which included the Brabender viscoamylograph, Bohlin CS rheometer, Brabender farinograph, WAXS, GPC, SEHPLC and Coulter counter have been used to examine the structural and behavioural characteristics of both cassava starch and flour. The results suggested that the functional behaviour of native cassava starches of different origins varies widely and appeared to be associated with molecular structure and the architecture of the starch granule. The viscosity and the mechanical properties of the pastes produced by gelatinization were determined by the degree of swelling and the amount and proportion of amylose and amylopectin in the solvent phase of the pastes. The amylopectin was present in the solvent phase in substantial quantities which varied between 37 and 57% of the total starch solubilized. In native cassava starches, the amylose appeared to have a high molecular weight (M, 19 x 105 - 11 x 105 ). The constituent chains of the amylopectin molecule did not vary in length with cassava starches of different origins, but their relative population did which was reflected in minor differences in the chromatographic profiles. Starch granules containing long chain amyloses and amylopectin with a high degree of branching were found to release reduced amounts of molecules into the liquid phase of the pastes, and vice versa Where the pastes contained a high proportion of amylopectin and long amylose molecules the resultant gel was surprisingly weak. Cassava starch processed to produce "sour" starch, or fermented, and sun dried starch, was found to have suffered degradation to an extent where 77-86 % of the starch was solubilized during aqueous heating. The extent of the degradation was influenced by the cassava cultivar. The "sour" starch proved superior to unfermented and fermented, oven dried starches in the production of baked baked products with an expanded texture. Starch extracted from cassava roots which had been stored for a short period, during which physiological deteriorative processes could have occurred, was found to show a slight reduction in the pasting viscosity which was not related to granular or molecular size or organization. Rural, factory-extracted starch was found to have a reduced paste viscosity as a consequence of fermentation and contamination with peel residues from the roots. Cassava flour properties were influenced by the conditions of preparation. Drying temperature, milling procedure and particle size could be selected and controlled to give cassava flours of the desired functional properties.